1994
DOI: 10.1128/jvi.68.9.6103-6110.1994
|View full text |Cite
|
Sign up to set email alerts
|

Virus-specific CD8+ cytotoxic T-lymphocyte activity associated with control of viremia in primary human immunodeficiency virus type 1 infection

Abstract: Human immunodeficiency virus type 1 (HIV-1) Env-, Gag-, Pol-, Nef-, and Tat-specific cytotoxic Tlymphocyte (CTL) activities were quantitated temporally in five patients with symptomatic primary HIV-1 infection. A dominant CD8+-mediated, major histocompatibility complex class I-restricted CTL response to the HIV-1 envelope glycoprotein, gpl60, was noted in four of the five patients studied. The level of HIV-1-specific CTL activity in the five patients paralleled the efficiency of control of primary viremia. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
429
2
14

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,729 publications
(452 citation statements)
references
References 43 publications
7
429
2
14
Order By: Relevance
“…Other studies have shown that most of the CD4 + T cell response can be captured by the combination of these 2 cytokines [21,22]; if IFN-g alone is used as the end point, a portion of the CD4 + T cell response is missed. CD8 + T cells are key effectors for clearing virus-infected cells [23] and have been associated with Downloaded from https://academic.oup.com/jid/article-abstract/194/12/1650/810944 by guest on 30 April 2020 control of lentivirus replication in both nonhuman primates (NHPs) and humans [24][25][26][27][28][29][30][31][32]. Twelve (34%) of the 35 vaccine recipients who received the 4-mg or 8-mg doses had detectable HIV Env-specific CD8 + T cell responses at week 12.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that most of the CD4 + T cell response can be captured by the combination of these 2 cytokines [21,22]; if IFN-g alone is used as the end point, a portion of the CD4 + T cell response is missed. CD8 + T cells are key effectors for clearing virus-infected cells [23] and have been associated with Downloaded from https://academic.oup.com/jid/article-abstract/194/12/1650/810944 by guest on 30 April 2020 control of lentivirus replication in both nonhuman primates (NHPs) and humans [24][25][26][27][28][29][30][31][32]. Twelve (34%) of the 35 vaccine recipients who received the 4-mg or 8-mg doses had detectable HIV Env-specific CD8 + T cell responses at week 12.…”
Section: Discussionmentioning
confidence: 99%
“…Passive transfer of a variety of anti-HIV1-Env antibodies to macaques induces complete or partial protection following vaginal SHIV challenge [34]. Additionally, the decrease of HIV levels in the blood has been associated with high levels of HIV-specific CD8 + T cell activity [35,36] and CD8 + T cell depletion in SIV-infected rhesus macaques causes an increase in plasma viremia [37,38]. Of note, following SIV infection of a natural host there is a general absence of chronic immune activation and this may need to be emulated by candidate vaccine vectors in order to generate appropriate immunity [39].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on acute HIV-1 infections [21,22] showed that early elevation of CD8 + CTL specific for HIV-1 can be observed several weeks after infection, corresponding to the initial decline of HIV-1 plasma viraemia, thus suggesting that CD8 + CTL plays important roles in controlling the virus replication in initial period of HIV-1 infection. Similarly, detections on clinical longterm nonprogressors [23][24][25][26] infected by HIV-1 demonstrated the presence of low viral loads, slower decrease in CD4 + T lymphocyte counts and broad CTL immune responses, supporting the notion that CTL responses may help to curb viral replication in these chronically HIV-1-infected individuals.…”
Section: Discussionmentioning
confidence: 99%